Potensi Murraya keonigii sebagai Herbisida Alami - Lussana Rossita Dewi; Praptining Rahayu (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2021)
Various kinds of agricultural products are needed to support organic farms to produce superior quality products, one of it was natural herbicides. Some plants have the potential to become natural herbicides by producing chemical compounds, namely allelopathy which can inhibit the growth of surrounding plants and Murraya keonigii is one of it. This study aims to see the potential of M. keonigii to become a natural herbicide. Grass seeds were given M keonigii’s extract at a dose of 0 gr / l (control / M0), 50 gr / lt (M1), 60 gr / lt (M2), and 70 gr / lt (M3). The results showed that the aromatic or allelopathic compounds in M ​​keonigii affected the germination. Germination was slower at doses of 60 gr / l (M2) and 70 gr / lt (M3) compared to controls (M0) and 50 gr / lt (M1). Radicle length did not increase rapidly in M2 and M3 treatment. Germination power of grass seeds in control and M0 had a value of 100% or all germinated, while M1 and M2 had 67% germination. The higher the dose of M keonigii extract, the slower the process of grass seed germination.